The Operational Principle and Problem Frames - Jackson, Michael (Reflections on the Work of C.A.R. Hoare, 2010)
In the problem frames approach to software development as its name indicates analysis of theproblem precedes construction of thesolution. The problem analysis rests on certain ideas of structure and simplicity, including a general recommendation that composition should be postponed until the parts to be composed are well understood in their preliminary isolated forms. These ideas are discussed in the light of Michael Polanyi’s notion of theoperational principle of a machine orcontrivance, and his account of the relationship between scientific knowledge and understanding of machines. Criteria are suggested for simplicity in problem decomposition. The outline structure of the associated development approach is sketched, and the relationship between formal development methods and problem structuring is clarified.